Comparison of tympanic membrane grafting medial or lateral to malleus handle - Mehrdad Rogha; Nezamoddin Berjis; Ali Taherinia; Afrooz Eshaghian (Advanced Biomedical Research, 2014)
Background: To compare two methods of tympanic membrane (TM) grafting when graft materials medial or lateral to malleus, this study have been done. Materials and Methods: In this clinical trial which was conducted in Alzahra and Kashani hospitals, between June 2010 and February 2012, 56 patients with chronic otitis media and perforated TM entered the study in two groups. The inclusion criteria consisted of patients who were at least 15-years-old without history of smoking, diabetes mellitus or autoimmune disease. Exclusion criteria of the study: No compliance for follow up, post-surgical ear trauma or any infective pathology that directly affects the ear. In Group A patients, the graft material is pierced in near central part of the graft and they lodged so that the malleus handle projects through the graft perforation. Group B had grafting in the lateral side of the malleus. Three month after surgery both groups examined and tested by audiometry. Success of surgery is defined as complete repair of TM, without lateralization, atelectasis, blunting or retraction pocket. Results: This study contained 28 patients in Group A and 28 in Group B. Overall success rate was 94.64% that was 96.42% in Group A, and 92.85% in Group B. Differences of air-bone gap in each group before and after surgery was 16.10 (±4.89) in Group A, and 15.78 (±3.40) in Group B. Improvement of hearing level was not significant between two surgical methods (P = 0.442). Conclusions: Both techniques (medial and lateral to malleus handle) of TM grafting are effective with success rates 96.42% and 92.85% respectively.